Effects of Temperature, Polymer Dose, and Solid Concentration on the Rheological Characteristics and Dewaterability of Digested Sludge of Wastewater Treatment Plant (WWTP) - Yeneneh, Anteneh; Hong, Eugene; Sen, Tushar; Kayaalp, A.; Ang, Ha Ming (Springer International Publishing, 2016)
The rheology of digested sludge affects the flow hydrodynamics, dewaterability, and the polymer consumption in wastewater treatment plants. The rheological characteristics of digested sludge are highly dependent on changes in total solid concentration, temperature, and polymer dose. Hence, this study aims at investigating the impacts of total solid concentration, temperature, and polymer dose on the rheological characteristics and the dewaterability of digested sludge. Investigating the relationship between rheological and physicochemical characteristics of sludge can also serve as a tool to optimize essential process parameters. Different homogenized digested sludge samples were subjected to rheological measurement on rotational stress-controlled rheometer equipped with Peltier concentric cylinder system. The shear stress–shear rate and viscosity–shear rate curves were then developed before and after polymer conditioning at various temperatures and solid concentrations.Different rheological model were fitted to the shear stress–shear rate and viscosity–shear rate rheograms, and the model with the best fitting and more practical significance was selected to determine key rheological parameters. The relationship between dewaterability and digested sludge rheology was also developed. The rheological characteristics of digested sludge during polymer conditioning and flocculation process was significantly affected by temperature and solid concentration; hence, polymer dose can be reduced by operating the dewatering process at optimum temperature condition and varying the polydose as a function of the total solid concentration and viscosity of the digested sludge. The dewaterability as measured in capillary suction time (CST) improved with increasing polymer dose up to 12 kg/t DS but further increase in polymer dose resulted in the deterioration of the dewaterability due to overdosing.